PERAN KOMUNITAS DALAM MENGAJARKAN SHOLAT BAGI MUALAF DI KOTA BENGKULU - Suryani, Bella; Khoiri, Qolbi; Haryono, Haryono (Jurnal Ilmu Pendidikan Islam, 2025)
Convert communities play an important role in guiding and assisting new Muslims in understanding and practicing Islamic worship,especially prayer (sholat). This study aims to describe the role of the community in teaching prayer to new Muslims in Bengkulu City. The issues raised include the community's development programs, the implementation of prayer guidance, and the experiences of new Muslims in performing prayer after joining the community. This study used a descriptive qualitative approach with observation, in-depth interviews, and documentation methods. The results show that the Fii Sabilillah Bengkulu Mualaf Foundation has a religious development program that includes guidance on reading the Quran, training in prayer practices, regular religious study sessions, and spiritual and social support. This program is designed to address the needs of new Muslims who generally still have limited understanding of worship procedures, especially prayer, which is an obligatory pillar of Islam. Guidance is implemented through regular meetings at the learning house, individual mentoring, and the provision of practical materials using methods tailored to the participants' abilities. The experiences of new Muslims in performing prayer after joining the community show positive developments, both in terms of reading comprehension, prayer movements, and spiritual awareness. Obstacles faced include awkwardness, limited memorization, and social barriers from their families or communities of origin. However, community support can provide a sense of security, motivation, and togetherness, enabling converts to adapt to Islamic teachings more firmly. Thus, the community plays a crucial role as a bridge for ongoing spiritual and social development for converts in Bengkulu City.